THE USE OF MOTORBIKE AS A MEANS OF GOOD TRANSPORTATION IN GRAB EXPRESS SERVICE AS SEEN FROM THE TRANSPORTATION LAW - Hilda Yunita Sabrie; Dina Kusuma Ratih; Prawitra Thalib (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2018)
The demand for goods delivery services in Indonesia is very large. Through this service, an item can easily move from one location to another and can be utilized so that the item has more value. Freight forwarding services can not be separated from the role of motor vehicles used as a means of transport. When viewed from the classification of its type, motor vehicles consist of motorcycles, passenger cars, freight cars, bus cars and special vehicles. In the relevant regulations stipulate that the goods delivery service must be carried out using the goods car. The obligation to use the goods car that has been regulated by law is not without reason. By using freight cars, bad weather factors and shock factors due to damaged road conditions can be avoided. This can minimize the risk of damage to the goods. But in practice it is often found that the delivery of goods is done using another mean of transporation that is motorcycle. The use of motorcycles is considered more effective and efficient because it can reach even remote areas. Although assessed so, the use of motorcycles can not avoid if there are two factors as mentioned above. Then this can lead to the risk of damage to the goods. Meanwhile, the delivery of goods must be implemented properly so that the goods can be saved and secured to the destination.